2012
DOI: 10.1534/genetics.111.137315
|View full text |Cite
|
Sign up to set email alerts
|

“Calling Cards” for DNA-Binding Proteins in Mammalian Cells

Abstract: The ability to chronicle transcription-factor binding events throughout the development of an organism would facilitate mapping of transcriptional networks that control cell-fate decisions. We describe a method for permanently recording protein-DNA interactions in mammalian cells. We endow transcription factors with the ability to deposit a transposon into the genome near to where they bind. The transposon becomes a "calling card" that the transcription factor leaves behind to record its visit to the genome. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 39 publications
4
97
0
Order By: Relevance
“…We found that 92.8% of the bat piggyBat sites had a flanking TTAA, which is slightly lower than the 96% observed with insect piggyBac in the human colorectal cancer line HCT116 cells (18) and the 98% observed with insect piggyBac in HeLa cells (17). The distribution of piggyBat and insect piggyBac insertions with respect to particular human chromosomal features was also similar (P = 0.11, χ 2 test; Fig.…”
Section: Resultsmentioning
confidence: 59%
“…We found that 92.8% of the bat piggyBat sites had a flanking TTAA, which is slightly lower than the 96% observed with insect piggyBac in the human colorectal cancer line HCT116 cells (18) and the 98% observed with insect piggyBac in HeLa cells (17). The distribution of piggyBat and insect piggyBac insertions with respect to particular human chromosomal features was also similar (P = 0.11, χ 2 test; Fig.…”
Section: Resultsmentioning
confidence: 59%
“…piggyBac inserts at target sites with the sequence TTAA but displays little selectivity for particular regions of the genome other than a modest preference for regions of DNase I sensitivity (16,17). A useful modification of PB would be to be able to guide integrations to safe harbor sites.…”
Section: Intmentioning
confidence: 99%
“…A useful modification of PB would be to be able to guide integrations to safe harbor sites. Others have shown that PB is distinguished by its ability to remain active when fused to a DNA binding domain and that such fusions can bias insertion toward cognate sites (10,16,18). Notably, Wilson and colleagues (19) fused a zinc finger protein (ZFP) targeted to the upstream promoter region of the cell-cycle checkpoint kinase 2 protein-coding gene CHEK2 to the native insect-derived piggyBac (iPB) transposase.…”
mentioning
confidence: 99%
“…The only inputs it requires are one expression profile of the initial state, one expression profile of cells in the target state, and an approximate transcriptional regulatory map indicating the direct targets of each TF. The network map can be derived from gene expression data by NetProphet (14) or other network inference algorithms, from TF binding motifs determined in vitro, or from in vivo binding data derived by methods such as chromatin immunoprecipitation sequencing (ChIP-seq) or Calling Cards (15,16). Unlike the CellNet recommendation system (8), NetSurgeon considers all genes that are DE between the initial and target states, not only those that increase, it considers interventions on all TFs whether or not they are DE, and it has no bias toward TFs with large numbers of targets.…”
Section: Significancementioning
confidence: 99%